(untitled) (Global Journal of Human-Social Science, 2016)
The colonial process which brought the coloniser and the colonised into a long period of co-existence and cohabitation which led to a master-servant relationship was not without major effects on the colonised up to the post independence era. As a way of curbing these effects on the colonised mentality, African writers, Nigerian inclusive have resorted to writing of works that would incorporate the use of cultural artifacts so as to depict their image and true identity. Through the lens of post-colonialism this herculean task of looking inwards and making use of that which is African, is made possible. Post-colonial theory is used to examine the ramifications of colonisation for both the coloniser and the colonised, as portrayed in the novel, Fearless of Ifeoma Chinwuba. The paper therefore, concludes that it is only when the colonised people begin to look inwards and appreciate the things that make them who they are culturally, that the recuperation of African culture as against western ideologies can positively be achieved. The textual analysis is specially based on the post-colonial discourse elements of hybridity, appropriation, abrogation, untranslated words and affiliation.